2022
DOI: 10.1021/acs.bioconjchem.1c00561
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Biomolecular Drug Designs Stabilized through Improved Thiol Conjugation and a Modular Locked Nucleic Acid Functionalized Assembly

Abstract: Albumin-nucleic acid biomolecular drug designs offer modular multifunctionalization and extended circulatory halflife. However, stability issues associated with conventional DNA nucleotides and maleimide bioconjugation chemistries limit the clinical potential. This work aims to improve the stability of this thiol conjugation and nucleic acid assembly by employing a fasthydrolyzing monobromomaleimide (MBM) linker and nucleaseresistant nucleotide analogues, respectively. The biomolecular constructs were formed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Increased recycling was observed for EgA1 and Atto647 functionalized assemblies compared to the non-functionalized designs. We have previously also observed increased cellular recycling of a fluorophore functionalized albumin-duplex assembly . It is speculated that the inclusion of fluorophores could mediate hydrophobic interactions with the cell membrane and that these additional cellular interactions could increase the internalization and subsequent recycling of the functionalized construct.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Increased recycling was observed for EgA1 and Atto647 functionalized assemblies compared to the non-functionalized designs. We have previously also observed increased cellular recycling of a fluorophore functionalized albumin-duplex assembly . It is speculated that the inclusion of fluorophores could mediate hydrophobic interactions with the cell membrane and that these additional cellular interactions could increase the internalization and subsequent recycling of the functionalized construct.…”
Section: Discussionmentioning
confidence: 88%
“…Previous work using a two-strand system showed high stability even in 50% serum. 11 However, disassembly of the annealed HJ construct under physiological conditions in vivo cannot be discounted and may have contributed to the shorter than expected half-life extension, as discussed above. Future work could address inclusion of other stabilized nucleotide analogues or different sizes and architectures of the assembly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albumin was chosen as the model protein, as it contains one free thiol available for selective modification using thiol-selective reagents . Furthermore, it is highly relevant, as conjugation of albumin is a tool for half-life extension of drugs and biomacromolecules. , For the experiments we prepared maleimide, MBM and SMCC modified DNA on a 20 nmol scale and purified the conjugates by reverse-phase HPLC. Analytical HPLC of the crude products of the maleimides showed only one major peak (Figure A, Figure S14), and LC-MS analysis of the purified DNA confirmed that the desired products were formed (Figure B, Figure S15).…”
Section: Resultsmentioning
confidence: 99%